An investigation on an approach for formalising rotation savings as a strategy for deposit mobilisation in the Zimbabwe financial services sector - Hove, Amen (Midlands State University, 2015)
Financial institutions play a vital role of crafting strategies designed to increase the saving propensity in a given country. The main objective of the study was to investigate on an approach Zimbabwe financial institutions can adopt to formalise rotation savings as a measure to enhance deposit mobilisation. The research was instigated as responses to a growing informal sector that habitat a robust saving product known as rotation savings. Rotation savings have the overall effect of inhibiting funds from trickling back in the formal economy and as such should be formalised. The researcher used both theoretical and empirical literature to review on approaches that were adopted in other countries, the framework that necessitated formalisation and supporting instruments engaged during the transition. As a result, the researcher used a descriptive research design because of its ability to describe and an explorative research design since no formal records exist in relation to the practise in Zimbabwe. A sample size of fifteen bank managers and eighty five members of the general populace were used to give a total of 100 respondents. Purposive sampling and Snow ball sampling were employed to issue out questionnaires to the general populace and a census was undertaken for interviews with bank managers. Both primary data and secondary were amalgamated and analysed through the use of Excel and Stata version 12. Research results revealed that savings are following a declining trend. The general populace depict a low motivation to save as they do not frequently employ bank services in terms of deposits per month. The fragmented savings behaviour was explained by inefficient strategies banks employ to lure deposits, hence making it necessary for banks to assess household behaviour in order to improve on their strategies. Results also show that formalisation in Zimbabwe can be instituted in one of two ways, that is, enacting a legislature or registering rotation savings as non-profit making organisations. The framework to be incorporated would have to factor into account issues to do with taxes, registration fees and registration paperwork. Consequently, results also show that consumer education would be very instrumental in facilitating a smooth transition in the formalisation process. The study therefore recommends the use of enacting a legislature as an approach towards formalising rotation savings. The legislature has to be flexible in terms of low registration fees and taxes. Consumer education and awareness has also been recommended as a tool that can be employed to create shared understanding of purpose between the general populace and financial institutions.